Quality parameters studies on Mangifera genus and varieties - Bihari, Man; Kumar, R.; Singh, K.; Kumar, A.; Prasad, A.; Narayan, Surya; Pandey, S.K.N. (Indian Journal of Horticulture, 2012)
Quality parameters was 50 mango species/varieties showed highest weight and volume per fruit in variety Star, and the lowest in Sinchittli. Specific gravity of fruit (1.06) was found the maximum in varieties Kailwa Champa and Mohan Thakur, while was lowest in Himayuddin and Bhagalshah. The maximum acidity content was recorded in Lal Bhadyana and Sinchittli, while it was minimum in Roadwala. Total soluble solids content was found the maximum in Faizwala () and the minimum in Star () and Mangifera odorata (). The highest total sugars content was estimated in Faizwala and minimum in Mangifera zeylanica (). Non-reducing sugar content was observed maximum in Amrapali, whereas it was recorded minimum in Roshan Tawak (). The maximum reducing sugar content was found in varieties Singra and Saunfia (). Mangifera zeylanica and Riyat No. 1 revealed minimum content. Ascorbic acid content was found the maximum in Mangifera zeylanica (), and it was found the lowest in Mangifera odorata (). All the above results showed a great diversity for different quality characteristics, which can be taken up for making improvement.